PENERAPAN AKAD MURABAHAH PADA PEMBIAYAAN KPR SYARIAH DI BANK SUMUT SYARIAH CABANG RINGROAD MEDAN SELAYANG - Rizky Nur Safitri; Nahar Alang Abdul Ghani; Eli Agustami (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2022)
A house is a basic human need, but the soaring house prices rarely make people able to buy a house in cash. This is where the Bank bridges the interests of home buyers and sellers by offering mortgage products (House Ownership Credit), but the interest system used in conventional banks is a usury transaction which is prohibited for Muslims. The emergence of Islamic banking is a positive thing for Muslims who need facilities from usury-free banking. However, the development of Islamic banks in Indonesia is still far below that of conventional banks, this is an illustration that most of the Muslim community in Indonesia do not fully believe in using Islamic banks. On this basis, the author examines and discusses the application of the murabahah contract in Islamic mortgage financing at the North Sumatra Islamic Bank branch Ringroad Medan Selayang. This research is a descriptive qualitative research with case study theory which aims to describe the application of murabahah contracts to Islamic mortgage financing at the North Sumatra Islamic Bank Ringroad Medan Selayang branch and to find out how the implementation of murabahah contracts in Islamic mortgage financing at Bank Sumut Syariah Ringroad Medan Selayang Branch and how the impact of the implementation of the murabahah contract on Islamic mortgage financing at Bank Sumut Syariah Ringroad Medan Selayang Branch. Techniques for collecting data using interview techniques, namely by conducting questions and answers with officers, employees and authorities (authorized) and documentation to seek information regarding the implementation of murabahah contracts in Islamic mortgage financing. The data analysis technique used descriptive method. The results of this study, the implementation of the DSN-MUI fatwa on murabahah on the practice of murabahah financing in Sharia mortgage financing carried out by the Harmoni branch of BTN Syariah is appropriate and implemented especially in the murabahah bil wakalah financing model and treatment for defaulting customers..